Women's literary networks and Romanticism : "a tribe of authoresses" - Winckles, Andrew O.; Rehbein, Angela (Romantic reconfigurations., 2017)
Andrew O. Winckles is Assistant Professor of CORE Curriculum (Interdisciplinary Studies) at Adrian College. Angela Rehbein is Associate Professor of English at West Liberty University.